TELAAH KEPEMILIKAN KEBENARAN ILMIAH PADA PENGEMBANGAN PENGETAHUAN AKUNTANSI - suhardi suhardi (JEM Jurnal Ekonomi dan Manajemen, 2017)
This article aims to examine the conflicting paradigm in accounting research and development from the point of view of the philosophy of science. Each adherent is both mainstream and alternative, assuming that their point of view is the most scientific approach and more suitable for developing the discipline of accounting scholarship. This article also agrees on the use of a multiparadigm approach as a space for researchers so that it does not have to be trapped in a single point of view, it would be better to paradigm each other interact and synergize to produce strength. Accounting research and development can be approached from the point of view of the philosophy of science. From any point of view the paradigm used in researching and developing whether the mainstream or accounting alternative is a product of knowledge that has no absolute truth, so it is not necessary to differentiate the way of view in researching accounting into a contradiction that can negate the essence of epistemology, ontology, and axiology